This question was previously asked in

SSC CGL Previous Paper 21 (Held On: 16 August 2017 Shift 3)

Option 4 : 5√3

**Given:**

x = √{(2 + √3)/(2 - √3)}

**Formula Used:**

(a + b) × (a – b) = a^{2} – b^{2}

(a + b)2 = a2 + 2ab + b2

**Calculation:**

x = √{(2 + √3)/(2 - √3)}

Rationalizing this

x = √{(2 + √3)^{2}/(2 + √3) × (2 - √3)}

⇒ √{(2 + √3)^{2}/(4 – 3)}

⇒ x = 2 + √3

Put this in the expression x^{2} + x – 9

⇒ (2 + √3)^{2} + (2 + √3) – 9

⇒ 4 + 3 + 4 √3 + 2 + √3 – 9

⇒ 5 √3

SSC CPO Paper 1 2020: Full Mock Test

43587

200 Questions
200 Marks
120 Mins